Pengaruh Gaya Kepemimpinan Chairul Tanjung Terhadap Kinerja Karyawan Pada Perusahaan CT Crop - Aprinawati Aprinawati; Grestin Analia Br Togatorop; Regita Cahyani Br Karo Sekali; Samuel Indra Sitorus; Silvia Putriani Silitonga; Imamul Khaira (Departement of Mathematics Education, 2024)
This research aims to examine the basic concepts of organizational behavior with a focus on the meaning, objectives, levels of analysis, and managerial implications. Using a literature approach, this research reviews relevant literature in three journals related to organizational behavior and leadership. Based on the results of the analysis, it was found that a deep understanding of organizational behavior is very important to increase managerial effectiveness in organizations. This study also highlights how leadership style and organizational culture influence human resource performance, as well as how psychological and sociological approaches can be applied in the management of educational organizations.